2020
DOI: 10.31124/advance.11497014.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of comorbid psychiatric disorders among people with autism spectrum disorder: An umbrella review of systematic reviews and meta-analyses

Abstract: <p>With ever-increasing prevalence of various mental disorders worldwide, a comprehensive evaluation of the prevalence of co-occurring psychiatric disorders among individuals with autism spectrum disorder (ASD) is needed to strengthen the knowledge base. This umbrella review aims to summarize the current evidence on the prevalence of comorbid psychiatric disorders among people with ASD. A systematic search of 12 major databases and additional sources was conducted. Any systematically conducted narrative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
(73 reference statements)
0
40
0
Order By: Relevance
“…Rates of co morbid PsD in ASD population, possibly more with atypical affective disturbances [86], present a wide range and vary from 3.6-60% [87]. Also, in a recent umbrella review, the prevalence of schizophrenia spectrum and other psychotic disorders reported in eight systematic reviews and meta-analyses including adults with ASD ranged from 4-67% [25]. The study design and the characteristics of our sample might explain the low rates found in our study.…”
Section: Psychotic Disorder (Psd)mentioning
confidence: 55%
“…Rates of co morbid PsD in ASD population, possibly more with atypical affective disturbances [86], present a wide range and vary from 3.6-60% [87]. Also, in a recent umbrella review, the prevalence of schizophrenia spectrum and other psychotic disorders reported in eight systematic reviews and meta-analyses including adults with ASD ranged from 4-67% [25]. The study design and the characteristics of our sample might explain the low rates found in our study.…”
Section: Psychotic Disorder (Psd)mentioning
confidence: 55%
“…Since 2015, many umbrella reviews have been conducted evaluating the evidence base on the psychosocial epidemiology of mental health in diverse populations [19][20][21][22][23][24]. However, no umbrella review or review of the reviews was found, which can inform the mental health implications of quarantine and isolation for infection prevention at the global landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric comorbidity in ASD is still under-investigated, even if nearly 70% of people with ASD, including children and adolescents, experience at least one comorbid psychiatric disorder, and around 40% may have two or more psychiatric disorders [ 9 , 26 , 27 ]. Regarding the different comorbidities in ASD, the prevalence of mood disorder among 21,797 participants with ASD has been reported as 18.8% (95% CI: 10.6–31.1) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%